Enhancement of β‐carotene‐rich carotenoid production by a mutant Sporidiobolus pararoseus and stabilization of its antioxidant activity by microencapsulation. Issue 8 (4th June 2020) - Manowattana, Atchara; Techapun, Charin; Laokuldilok, Thunnop; Phimolsiripol, Yuthana; Chaiyaso, Thanongsak
Abstract: The effective enhancement of β‐carotene production by Sporidiobolus pararoseus KM281507 was successfully achieved by random mutagenesis using ethyl methanesulfonate (EMS) combined with light irradiation. The mutant S. pararoseus E47 obtained from EMS mutagenesis produced a promising yield of biomass, β‐carotene, and total carotenoids under white light (1, 000 Lux). The maximal biomass (19.76 g/L), β‐carotene (128.97 mg/L), total carotenoids (179.72 mg/L), and β‐carotene content (72%, w/w) of the total carotenoids were obtained. The β‐carotene‐rich carotenoids were extracted from yeast cells and encapsulated in alginate beads using a new encapsulation method to enhance its stability, revealing an effective concentration of 0.5% alginate + 1.0% vitamin C. The half‐life of this β‐carotene was 13 and 68 days for un‐encapsulated and encapsulated + 1.0% vitamin C at 4°C with 1, 000‐Lux light irradiation, respectively. This result could uncover a potential alternative β‐carotene source and its further application in foods, animal feeds, and cosmetic industries. Practical applications: The carotenoid extract of S. pararoseus mutant E47 was rich in β‐carotene (72%, w/w). After extraction, the β‐carotene‐rich carotenoids were very sensitive to light and oxygen; thus, they were stabilized using a microencapsulation technique. To enhance their stability, vitamin C was added in the alginate phase making the β‐carotene‐rich carotenoid alginate beads (BCAB) highly stable and simply used for many applications including foods, feeds, cosmetics, and medicines.